Phlorotannins: Novel Orally Administrated Bioactive Compounds That Induce Mitochondrial Dysfunction and Oxidative Stress in Cancer - Layla Simón; Migdalia Arazo-Rusindo; Andrew F. G. Quest; María Salomé Mariotti-Celis (MDPI AG, 2023)
Mitochondrial dysfunction is an interesting therapeutic target to help reduce cancer deaths, and the use of bioactive compounds has emerged as a novel and safe approach to solve this problem. Here, we discuss the information available related to phlorotannins, a type of polyphenol present in brown seaweeds that reportedly functions as antioxidants/pro-oxidants and anti-inflammatory and anti-tumorigenic agents. Specifically, available evidence indicates that dieckol and phloroglucinol promote mitochondrial membrane depolarization and mitochondria-dependent apoptosis. Phlorotannins also reduce pro-tumorigenic, -inflammatory, and -angiogenic signaling mechanisms involving RAS/MAPK/ERK, PI3K/Akt/mTOR, NF-κB, and VEGF. In doing so, they inhibit pathways that favor cancer development and progression. Unfortunately, these compounds are rather labile and, therefore, this review also summarizes approaches permitting the encapsulation of bioactive compounds, like phlorotannins, and their subsequent oral administration as novel and non-invasive therapeutic alternatives for cancer treatment.